Trigeminal Neuralgia Caused by Cerebellopontine Angle Tumors: Surgical Series - Meguins, Lucas Crociati; Rodrigues, Thayanna Bentes Lemanski Lopes; Caramanti, Ricardo Lourenço; Rocha, Carlos Eduardo Dale Aglio; Laurenti, Matheus Rodrigo; Góes, Mario José; de Moraes, Dionei Freitas; Tognola, Waldir Antonio (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Introduction Cerebellopontine angle (CPA) tumors represent an important cause of persistent and refractory trigeminal neuralgia (TN). It is believed that ∼ between 1 and 9.9% of the cases of patients presenting with TN painful manifestation are caused by space-occupying lesions.Objective The objective of the present study is to describe the clinical and surgical experience of the operative management of patients presenting with secondary type TN associated with CPA tumors.Method An observational investigation was conducted with data collection from patients with secondary type TN associated with CPA tumors who were treated with surgical resection of the space-occupying lesion and decompression of the trigeminal nerve from January 2013 to November 2016 in 2 different centers in the western region of the state of São Paulo, Brazil.Results We operated on 11 consecutive cases in which TN was associated with CPA during the period of analysis. Seven (63.6%) patients were female, and 4 (36.4%) were male. Seven (63.6%) patients presented with right-side symptoms, and 4 (36.4%) presented with left-side symptoms. After 2 years of follow-up, we observed that 8 (72.7%) patients showed a complete improvement of the symptoms, with an excellent outcome, and that 3 (27.3%) patients showed an incomplete improvement, with a good outcome. No patient reported partial improvement or poor outcome after the follow-up. There was no operative mortality.Conclusion Cerebellopontine angle tumors represent an important cause of TN and must be included in the differential diagnosis of patients presenting with refractory and persistent symptoms. Surgical treatment with total resection of the expansive lesion and effective decompression of the trigeminal nerve are essential steps to control the symptoms.
Keywords: trigeminal neuralgia; cerebellopontine angle tumors